2021
DOI: 10.18632/aging.203288
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of fatty acid metabolism-related genes in patients with hepatocellular carcinoma

Abstract: The deregulation of fatty acid metabolism plays a crucial role in cancer. However, the prognostic value of genes involved in the metabolism in hepatocellular carcinoma (HCC) remains largely unknown. We first constructed a multi-fatty acid metabolic gene prognostic model of HCC based on The Cancer Genome Atlas (TCGA) and further validated it using the International Cancer Genome Consortium (ICGC) database. The model was integrated with the clinical parameters, and a nomogram was built and weighted. Moreover, im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…He et al. had explored FA metabolism-related risk genes in HCC by constructing a prognostic model but failed to further explore the role of these genes in the onset and progression of HCC ( 46 ). Identification of key molecular markers associated with FA metabolism and clarification of their roles in the progression of HCC is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…He et al. had explored FA metabolism-related risk genes in HCC by constructing a prognostic model but failed to further explore the role of these genes in the onset and progression of HCC ( 46 ). Identification of key molecular markers associated with FA metabolism and clarification of their roles in the progression of HCC is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…(AUC = 0.698) ( 28 ), Gao et al . (AUC = 0.614) ( 25 ), and He et al (AUC = 0.705) ( 26 ). Although our model was not as accurate as the models of Deng et al (AUC = 0.757) ( 24 ) and Shen et al (AUC = 0.737) ( 27 ), the gene number of our signature is much smaller than their ones (5 vs. 19 and 10, respectively).…”
Section: Resultsmentioning
confidence: 87%
“…In combination with previous studies ( 9 ), we obtained three gene sets (KEGG fatty acid metabolism pathway, Reactome fatty acid metabolism genes, and Hallmark fatty acid metabolism genes) from Molecular Signature Database v7.2 (MSigDB). The screening yielded 309 genes related to fatty acid metabolism ( Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that abnormal fatty acid metabolism leads to a variety of diseases (6). A growing number of researchers have found that fatty acid metabolism plays an important role in the recognition, occurrence, and progression of various cancers, including but not limited to breast, prostate, ovarian, liver, and colon cancers (7)(8)(9)(10). For example, dysregulation of fatty acid metabolism may interfere with the efficacy of chemotherapy and radiotherapy and immunotherapy in breast cancer patients (11).…”
Section: Introductionmentioning
confidence: 99%